Analysis of Flow Capacity of Liufangdi Section of Main Stream of the Huaihe River Based on MIKE 11 and 21 Models - WANG Kaizhen (Renmin Zhujiang)
In order to analyze the flow capacity for the north and south braided channels and upper and lower flooding areas of Liufangdi section of the main stream of the Huaihe River,this paper establishes this one- and two-dimensional hydrodynamic model for main stream of Huaihe from Xiashankou to upper section of Tangyu Lake based on the MIKE 11,21 software,performs a flood diversion simulation on those channels and flooding areas,and determines that the flow capacity of the channel from Xiashankou to upper Liufangdi section cannot meet the design requirements,and the flood discharge capacity of the upper Liufangdi flooding area cannot reach the flood discharge volume required in the Huaihe flood dispatching scheme according to simulation and calculation results of model.The model also serves as the technical support for the adjustment and construction plan of the upper and lower Liufangdi flooding areas.